GEOCHEMISTRY OF SEDIMENTS AND ENVIRONMENT IN XIHU LAKE OF GREAT WALL STATION OF CHINA, ANTARCTICA - XIE, YY; GUAN, P; YANG, SJ; CHEN, BR; YANG, YN (中国科学b辑 化学英文版, 1992)
The determined results in this paper, which were obtained by the multielement analysis of the 260 cm-deep core sediments under the water of Xihu Lake in the Great Wall Station area, are as follows: The Cenozoic volcanic rocks around Xihu Lake are the main source of sediments in the lake. The chemical differentiation in very fine particles is still detectable. From the variation of ratios of the Cs/Rb, Br/CI and La/Yb in the clay fraction with depth and from the variation or CaCo3 contained in the sediments, cation replacing amount in the clay grains and the sediment grain sizes in time, it can be seen that since 3600 a. B. P., there has existed the climatic variation of warm-cold-warm, which embodies the advance and retreat history of the ice sheet in this area. Chemistry, Multidisciplinary SCI(E) 3 ARTICLE 6 758-768 35